The little mermaid - Andersen Christian Hans (USBorne china, 2009)
The Little Mermaid is a fairy tale by Hans Christian Andersen that tells the story of a young mermaid princess who dreams of becoming human. She falls in love with a human prince and, to be with him, sacrifices her voice in exchange for legs from a sea witch. However, the transformation comes with great challenges, and the mermaid must win the prince's love or face tragic consequences. The story explores themes of love, sacrifice, and the quest for identity, ending in a bittersweet conclusion rather than the typical "happily ever after."